# How do you solve for x: #4x+12(-x-3) = 2x-4(-x)-3^2#?

Notice that a large part of solving this equation involves the correct order of operations as well. Maths is seldom little compartments, but one huge subject full of different concepts and methods, but they all intertwine.

By signing up, you agree to our Terms of Service and Privacy Policy

To solve for x in the equation 4x + 12(-x - 3) = 2x - 4(-x) - 3^2, follow these steps:

- Expand both sides of the equation.
- Combine like terms.
- Move all terms involving x to one side of the equation and constants to the other side.
- Solve for x.

Expanding both sides: 4x + 12(-x - 3) = 2x - 4(-x) - 9 4x - 12x - 36 = 2x + 4x - 9

Combining like terms: -8x - 36 = 6x - 9

Moving terms involving x to one side and constants to the other: -8x - 6x = 36 - 9 -14x = 27

Solving for x: x = 27 / -14

By signing up, you agree to our Terms of Service and Privacy Policy

- How do you solve #3x - 1( 5+ x ) = 2( x + 5)#?
- I go to the store to buy school supplies. I spend $8.52. I buy one notebook $2.55 and three pens which are each the same price. What is the price of a pen?
- How do you convert 1/8 to a decimal using long division?
- How do you solve #4x=24#?
- How do you express #84/162# in decimal to #3# decimal places ?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7